A Follow-up Study on BMI-SDS and Insulin Resistance in Overweight and Obese Children at Risk for Type 2 Diabetes Mellitus. (19th January 2015) - Fazeli Farsani, Soulmaz; van der Aa, Marloes P.; Knibbe, Catherijne A. J.; de Boer, Anthonius; van der Vorst, Marja M. J.
Objectives . To evaluate body mass index standard deviation score (BMI-SDS), insulin sensitivity, and progression to type 2 diabetes mellitus (T2DM) in children at risk for T2DM approximately 3 years after being diagnosed with overweight/obesity and insulin resistance (measured by Homeostasis Model Assessment of Insulin Resistance [HOMA-IR]). Methods . Out of 86 invited children, 44 (mean age 15.4 ± 3.6 years) participated. Medical history, physical examination, and laboratory workup were performed. Results . While the mean BMI-SDS significantly increased from 2.9 to 3.4, the mean HOMA-IR significantly decreased from 5.5 to 4.6 (baseline vs follow-up visit). Change in HOMA-IR was only due to a decrease in mean fasting plasma insulin (24.1 vs 21.1, P = .073). Conclusions . Although increase in BMI-SDS in these children is worrisome, the American Diabetes Association recommended screening interval of 3 years for children at risk for T2DM is not too long based on the fact that none of our study participants developed T2DM.